Short-term effects on lower-body functional power development: Weightlifting vs. vertical jump training programs - Tricoli, V.; Lamas, L.; Carnevale, R.; Ugrinowitsch, C. (The Journal of Strength and Conditioning Research, 2006)
Among sport conditioning coaches, there is considerable discussion regarding the efficiency of training methods that improve lower-body power. Heavy resistance training combined with vertical jump (VJ) training is a well-established training method; however, there is a lack of information about its combination with Olympic weightlifting (WL) exercises. Therefore, the purpose of this study was to compare the short-term effects of heavy resistance training combined with either the VJ or WL program. Thirty-two young men were assigned to 3 groups: WL = 12, VJ = 12, and control = 8. These 32 men participated in an 8-week training study. The WL training program consisted of 3 × 6RM high pull, 4 × 4RM power clean, and 4 × 4RM clean and jerk. The VJ training program consisted of 6 × 4 double-leg hurdle hops, 4 × 4 alternated single-leg hurdle hops, 4 × 4 single-leg hurdle hops, and 4 × 4 40-cm drop jumps. Additionally, both groups performed 4 × 6RM half-squat exercises. Training volume was increased after 4 weeks. Pretesting and posttesting consisted of squat jump (SJ) and countermovement jump (CMJ) tests, 10- and 30-m sprint speeds, an agility test, a half-squat 1RM, and a clean-and-jerk 1RM (only for WL). The WL program significantly increased the 10-m sprint speed (p < 0.05). Both groups, WL and VJ, increased CMJ (p < 0.05), but groups using the WL program increased more than those using the VJ program. On the other hand, the group using the VJ program increased its 1RM half-squat strength more than the WL group (47.8 and 43.7%, respectively). Only the WL group improved in the SJ (9.5%). There were no significant changes in the control group. In conclusion, Olympic WL exercises seemed to produce broader performance improvements than VJ exercises in physically active subjects.